1999
DOI: 10.1093/gerona/54.10.m494
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Rehabilitation and Exercise Strategies in the Nursing Home

Abstract: With both interventions, facilities were able to implement a broad-based intervention that resulted in a significant reduction in ADL decline rates. A facility-wide nursing rehabilitation program can play a useful role in reversing functional decline, helping residents to maintain their involvement in a broad spectrum of ADL activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 9 publications
2
91
2
Order By: Relevance
“…This meant that a resident transferred from bed to chair several times instead of once, completed a series of sit-to-stands in the resident's bedroom, the dining room and the lounge, and increased walking distances by taking a longer route to the dining room and incremental walking distances outside. The emphasis throughout was resident centred and followed the principle that incrementally increasing repetitions of exercises will increase activity tolerance and support goal attainment [10]. (iv) Health care assistant training:…”
Section: (Iii) Development Of Promoting Independent Plan (Pip)mentioning
confidence: 99%
See 2 more Smart Citations
“…This meant that a resident transferred from bed to chair several times instead of once, completed a series of sit-to-stands in the resident's bedroom, the dining room and the lounge, and increased walking distances by taking a longer route to the dining room and incremental walking distances outside. The emphasis throughout was resident centred and followed the principle that incrementally increasing repetitions of exercises will increase activity tolerance and support goal attainment [10]. (iv) Health care assistant training:…”
Section: (Iii) Development Of Promoting Independent Plan (Pip)mentioning
confidence: 99%
“…Recent randomised controlled trials have found inconsistent effects of physical training on physical performance in institutionalised older people. There is evidence to support physical training having a positive impact on muscle strength, aerobic capacity, flexibility and balance [9][10][11]. Exercises to improve strength, balance and endurance were included in the current programme; however, the intensity may not have been sufficient to result in measurable change in physical performance outcomes.…”
Section: K Peri Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…About 10% of the 3563 disabled residents were classified into the Rehabilitation category (RUGs 1-14), almost all falling into the medium and low intensity rehabilitation groups (RUGs 9-14). Most of these (82.7%) received some form of physical therapy aimed at preventing further decline of physical function (13), and only a small percentage (17.3%) received rehabilitation therapy after an acute event such as a stroke or hip fracture.…”
Section: Classification Of Residents Into Rugsmentioning
confidence: 99%
“…Exercise may slow the deterioration in physical and psychosocial domains in the elderly, 4,14,20-23 but exercise strategies in nursing homes and other long-term care facilities are not standardized. 24 Research has suggested that available programming should be increased substantially relative to what is recommended by guidelines. 25 Gaps in availability of exercise programming are apparent in institutional settings.…”
mentioning
confidence: 99%